The creativity of the J3K version of the Gojek advertisement in the covid 19 pandemic era - Untari Salsabila, Kania; Waliya Hamima, Naila; KN, Jamiati (Universitas Ahmad Dahlan, 2022)
In the middle of the covid pandemic people are required to stay at home and also sosial distancing, according to government policy about transportation control made gojek provide a new service namely J3K. The purpose of this research to analyze the creativity of gojek advertisement both in terms of appearance and content. To make customer feeling more safe and comfortable, in creative way to promote their service they use an animation for advertisements. In this case researcher uses a case study approach with qualitative and descriptive for describe, analyze, and interpret the J3K Gojek advertisement. The result of this search based on observation, literature study (books, journals, and websites), and documentation, Gojek succeeded get the attention of the public from their creativity advertisement can gather the trust of their users especially the Indonesia citizen